Colorimetric determination of tetracyclines based on aptamer-mediated dual regulation of gold nanoparticle aggregation and in situ silver metallization. Issue 18 (28th April 2022) - Liu, Dingmin; Huang, Pengcheng; Wu, Fang-Ying
Abstract : Schematic of colorimetric detection of tetracyclines based on dual regulation of gold nanoparticle (AuNP) aggregation and in situ silver metallization utilizing the catalytic properties of AuNPs and aptamer-target specific interaction. Abstract : A colorimetric assay was described for determination of tetracyclines (TCs) in complex matrices based on dual regulation of gold nanoparticle (AuNP) aggregation and in situ silver metallization. The reaction between p -aminophenol and silver ions (Ag + ) catalyzed by aptamer (Apt)-functionalized AuNPs promoted the in situ deposition of Ag shells on AuNPs to afford core–shell bimetallic NPs (Au@AgNPs). When the target is present, Apt is separated from the AuNP surface through the Apt-target interaction. With the desorption of Apts, AuNPs catalyzed the formation of more aggregated Au@AgNPs with a thinner Ag shell, corresponding to the solution color gradually changing from orange-yellow to brown. Using A 600 / A 410 as the determination signal, the assay gave visible linear relationships for TCs in the range of 0.3–6.0 μmol L −1 with a detection limit (LOD) of 33.6 nmol L −1 . In particular, the assay was successfully applied to detect TCs in real samples with the recovery rate ranging from 91.2% to 106% and relative standard deviation (RSD) less than 4.6%. These results meet the requirements of sample analysis.